Molecular mechanism underlying recruitment and insertion of lipid-anchored LC3 protein into membranes - Thukral, Lipi; Sengupta, Durba; Ramkumar, Amrita; Murthy, Divya; Agrawal, Nikhil; Gokhale, Rajesh S. (Biophysical Journal, 2015)
Lipid modification of cytoplasmic proteins initiates membrane engagement that triggers diverse cellular processes. Despite the abundance of lipidated proteins in the human proteome, the key determinants underlying membrane recognition and insertion are poorly understood. Here, we define the course of spontaneous membrane insertion of LC3 protein modified with phosphatidylethanolamine using multiple coarse-grain simulations. The partitioning of the lipid anchor chains proceeds through a concerted process, with its two acyl chains inserting one after the other. Concurrently, a conformational rearrangement involving the alpha-helix III of LC3, especially in the three basic residues Lys(65), Arg(68), and Arg(69), ensures stable insertion of the phosphatidylethanolamine anchor into membranes. Mutational studies validate the crucial role of these residues, and further live-cell imaging analysis shows a substantial reduction in the formation of autophagic vesicles for the mutant proteins. Our study captures the process of water-favored LC3 protein recruitment to the membrane and thus opens, to our knowledge, new avenues to explore the cellular dynamics underlying vesicular trafficking.